Desakan Kuasa dalam Penentuan Harga Jual - Ade Ikhlas Amal Alam; Iwan Triyuwono; Aji Dedi Mulawarman (Jurnal Ekonomi Modernisasi, 2018)
The presence of power in every line of life can not be avoided especially in the determination of the selling price in commerce. The purpose of this study is to trace the power of Yasdic's management in determining the selling price in the business unit of Santri Store of Pondok Pesantren Pendidikan Al-Qur'an IMMIM Putra Makassar. The methodology used in this study is a critical etnometodology combined with Islamic thinker Ibn Khaldun to trace the power of Yasdic in determining the selling price in the santri store business unit. Our research found that the power Yasdic determining the selling price to oppress buyers through an expensive price and a monopoly that supported the prevailing system in the cabin and conducted with no transparency.